Bidirectional plasticity of GABAergic tonic inhibition in hippocampal somatostatin- and parvalbumin-containing interneurons - Wyroślak, Marcin; Dobrzański, Grzegorz; Mozrzymas, Jerzy W. (Frontiers in Cellular Neuroscience, 2023)
GABAA receptors present in extrasynaptic areas mediate tonic inhibition in hippocampal neurons regulating thus the performance of neural networks. Here, we investigated the effect of NMDA-induced plasticity on tonic inhibition in somatostatin- and parvalbumin-containing interneurons. Using pharmacological methods and transgenic mice (SST-Cre/ PV-Cre x Ai14) we induced plasticity of GABAergic transmission in somatostatin- and parvalbumin-containing interneurons by a brief (3 min) application of NMDA. In the whole-cell patch-clamp configuration we measured tonic currents enhanced by specific agonists (etomidate or gaboxadol). Furthermore, in both control and NMDA-treated groups we examined to what extent these changes depend on regulation of distinct subtypes of GABAA receptors. Tonic conductance in the somatostatin-containing (SST+) interneurons is enhanced after NMDA application and the observed effect is associated with increased content of α5-containing GABAARs. Both fast-spiking and non-fast spiking parvalbumin-positive (PV+) cells showed reduction of tonic inhibition after the plasticity induction. This effect was accompanied in both PV+ interneuron types by a strongly reduced proportion of δ-subunit containing GABAARs and a relatively small increase in currents mediated by α5-containing GABAARs. Both somatostatin- and parvalbumin-containing interneurons show cell type-dependent and opposite sign plasticity of tonic inhibition. The underlying mechanisms depend on the cell-specific balance of plastic changes in contents of α5 and δ subunit-containing GABAARs.